Bioprotective properties of three Malaysia Phyllanthus species: an investigation of the antioxidant and antimicrobial activities - T., Poh Hwa; Cheah, Yoke Kqueen; J., Indu Bala; Radu, Son (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2011)
The aim of this work was to investigate the antioxidant and antimicrobial of Phyllanthus amarus, Phyllanthus niruri and Phyllanthus urinaria. P. niruri was found to possess the highest antioxidant activity, the activity decreased in the order P. niruri > P. amarus > P. urinaria for water extract. However, the activity decreased in the order P. niruri > P. urinaria > P. amarus for methanol extract. The result correlation between the antioxidant activity and total phenolic content revealed a positive correlation of 0.954 < r2 < 1.000 for both water and methanol extract. Methanol extract showed higher total phenolic content and antioxidant activity as compared with water extract. Lowest Minimum Inhibitory Concentration (MIC) value for water extract against the selected microorganism was >2.5 mg/mL meanwhile, for methanol extract was <0.625 mg/mL. MBC level >2.5 mg/mL and >0.625 mg/mL were the value for water and methanol extract. Methanol extract showed better inhibition potential than water extract.